Characterization of the nanosized porous structure of black Si solar cells fabricated via a screen printing process - 汤叶华 周春兰 王文静 周肃 赵彦 赵雷 李海玲 闫保军 陈静伟 费建明 曹红彬 (Journal of semiconductors, 2012)
A silicon（Si） surface with a nanosized porous structure was formed via simple wet chemical etching catalyzed by gold（Au） nanoparticles on p-type Cz-Si（100）.The average reflectivity from 300 to 1200 nm was less than 1.5%.Black Si solar cells were then fabricated using a conventional production process.The results reflected the output characteristics of the cells fabricated using different etching depths and emitter dopant profiles.Heavier dopants and shallower etching depths should be adopted to optimize the black Si solar cell output characteristics. The efficiency at the optimized etching time and dopant profile was 12.17%.However,surface passivation and electrode contact due to the nanosized porous surface structure are still obstacles to obtaining high conversion efficiency for the black Si solar cells.